INTERNATIONAL STUDENTS’ INTERCULTURAL COMMUNICATION EXPERIENCES AT A STATE UNIVERSITY IN JAMBI - Pranata, Kevin; Saharudin; Hustarna (Universitas Jambi, 2026)
Intercultural communication refers to the exchange of information between individuals from two different cultures. The purpose of this qualitative research was to explore the intercultural experiences of international students during their studies at a state university in Jambi. The study employed a qualitative method. Four international students from Myanmar, Egypt, and Pakistan were involved in this study. The data were gathered from audio-recorded interviews conducted via Zoom meetings, using an interview protocol, and were transcribed verbatim. Thematic analysis, as proposed by Braun and Clarke (2006), was employed to analyze the data. The findings revealed that international students faced various challenges, including ethnocentrism, language barriers and communication difficulties, stereotyping and generalization, and cultural shock. Understanding these experiences is crucial for enhancing the academic and social experiences of international students in a multicultural university environment.